2022
DOI: 10.1039/d2sm00685e
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine assisted non-monotonic jamming of colloids during evaporation induced assembly and its implication on CO2 sorption characteristics

Abstract: We report a detailed study of hierarchically organized silica-Polyethylenimine (PEI) microspheres achieved through the evaporation-induced assembly. Due to complex interactions between oppositely-charged silica nanoparticles and PEI, non-monotonic jamming of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…One way to extract the structural information from the scattering data is to perform model-dependent data analysis, where one tries to fit the scattering profile with standard equilibrium structure-factor models (such as that corresponding to hard sphere or sticky hard sphere potential) and obtain the associated parameters by the χ 2 minimization approach. In this direction, earlier most of the data from the spray-dried microgranules was fitted and reported in the literature. , However, employing the sticky hard sphere and hard sphere models for such highly dense and nonequilibrium systems is not a very reliable approach since these models are based on equilibrium liquid models. We can see from Figure S3 (Supporting Information) that by using these models we cannot obtain double-headed correlation peaks as in the present case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to extract the structural information from the scattering data is to perform model-dependent data analysis, where one tries to fit the scattering profile with standard equilibrium structure-factor models (such as that corresponding to hard sphere or sticky hard sphere potential) and obtain the associated parameters by the χ 2 minimization approach. In this direction, earlier most of the data from the spray-dried microgranules was fitted and reported in the literature. , However, employing the sticky hard sphere and hard sphere models for such highly dense and nonequilibrium systems is not a very reliable approach since these models are based on equilibrium liquid models. We can see from Figure S3 (Supporting Information) that by using these models we cannot obtain double-headed correlation peaks as in the present case.…”
Section: Resultsmentioning
confidence: 99%
“…In this direction, earlier most of the data from the spray-dried microgranules was fitted and reported in the literature. 68,69 However, employing the sticky hard sphere and hard sphere models for such highly dense and nonequilibrium systems is not a very reliable approach since these models are based on equilibrium liquid models. We can see from Figure S3 (Supporting Information) that by using these models we cannot obtain double-headed correlation peaks as in the present case.…”
mentioning
confidence: 99%
“…In order to further enhance the CO 2 capture efficiency, new strategies are being developed to produce solid sorbents. Among these strategies, evaporation-induced self-assembly of colloids of amine-bearing polymers, e.g., polyethyleneimine (PEI)-assisted silica nanoparticles, is highly apt for the production of highly porous sorbents with amine functionalities. Recently, we have shown that the CO 2 capture efficiency of these microspheres depends on their porosity as well as the loaded amine functionality . The evaporation-induced self-assembly of multicomponent colloids depends on complex interactions among the different components of the colloids. , As a result, the pore network and dynamics of polymers confined in the pore network of microspheres produced through the self-assembly of multicomponent colloids depend on various factors. Hence, it is imperative to investigate the pore architecture and dynamics of confined polymers within the pore network of self-assembled microspheres using complementary techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The tuning of the interaction between silica colloids and PEI molecules can dictate the nature of its binding in the silica microspheres. 42 The assembly of colloids in droplet drying is one well-established method to achieve nanostructured materials with the desired morphology. [42][43][44][45][46] The drying of micrometer-sized droplets containing silica colloids and PEI results in micrometer-sized mesoporous amine-silica microspheres in a single step.…”
Section: Introductionmentioning
confidence: 99%
“…42 The assembly of colloids in droplet drying is one well-established method to achieve nanostructured materials with the desired morphology. [42][43][44][45][46] The drying of micrometer-sized droplets containing silica colloids and PEI results in micrometer-sized mesoporous amine-silica microspheres in a single step. Thus, the silica-PEI microspheres, obtained through EIA, act as a support for the silver nanoparticles, which not only makes the synthesis procedure simple but also economical and environment friendly, and thus holds promise for the synthesis of metal-silica microspheres.…”
Section: Introductionmentioning
confidence: 99%